Identifikasi Hak Syuf’ah Terhadap Penambahan Modal Tanpa Hak Memesan Efek Terlebih Dahulu (PMTHMETD) - Helda Nusrida; Rozalinda (STIS DAFA MATARAM, 2022)
This research analyzes the implementation of the rights issue without preemptive rights (PMTHMETD) by PT Bumi Resources Tbk, focusing on the potential dilution effects on existing shareholders and its alignment with Islamic law, specifically the concept of syuf'ah (right of first refusal). Using a qualitative approach and library research method, the study examines relevant literature, regulations, and the DSN-MUI Fatwa No. 65/DSN-MUI/III/2008, along with secondary data from sources like www.idx.co.id and www.bumiresources.com. The findings reveal that the PMTHMETD led to a significant dilution of up to 58.8%, with 3.7% of shareholders opposing the decision. The research highlights the violation of syuf'ah rights as existing shareholders were not given the opportunity to purchase shares before they were offered to third parties, which could lead to unfair financial loss. The study recommends clearer regulation on the application of syuf'ah rights in capital market transactions to prevent potential harm to shareholders and ensure fairness in accordance with Islamic principles.